Exploring the Influence of Absorptive Capacity on Innovation: An Empirical Study of Large Industrial Companies in Syria - Bahlawan, Abd Al Azez Al (International journal of Engineering, Business and Management, 2023)
This paper investigates the impact of absorptive capacity on exploratory innovation in large industrial companies in Syria. The study employs a sample of 278 managers, and utilizes multiple regression analysis for the investigation. The results reveal a significant positive relationship between absorptive capacity and exploratory innovation. These findings highlight the importance of absorptive capacity as a strategic tool for enhancing exploratory innovation, and offer valuable insights for managers and policy-makers in industries facing dynamic and complex environments.